Le rôle de l'État dans l'élaboration des choix énergétiques et le rôle plus spécifique des différentes institutions publiques en France - Turpin, Dominique (Les Cahiers de droit, 1983)
This paper surveys the role of the key governmental institutions in the making of energy policy in France. It shows that in spite of fairly extensive debate of the issues in both chambers of the French National Assembly since the mid-1970s, members of parliament have so far failed to make a significant impact on decision-making in the field of energy. Part of this is due to the strength of the Cabinet's influence over the National Assembly, and to its constitutional position as policy-maker. Moreover, in spite of a vast array of departmental branches and associated agencies directly under ministerial authority, the government's power may have been more formal than real. Much of the actual decision-making is made by experts employed by the large State or privately-owned corporations. This extensive network of closely connected energy-producing corporations appears to have been, and to remain, the real seat of power, in spite of recurrent hopes for, and attempts at, democratization.